THE RELATIONSHIP BETWEEN INDONESIAN GDP, TOURISM RECEIPTS, AND FOREIGN TOURIST ARRIVALS - Syahputra, Ridho Ary (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Tourist activities are considered to be one of the sources of economic growth in the world income. On an international scale, tourism has been recognized as the largest export in trade for many nations. At the country level, tourism has enabled economic restructuring by shifting the labor force from primary sectors such as agriculture and manufacturing to the service sectors. Tourist activities are also part of the economic growth to develop the infrastructures or add new destinations and landmarks to attract more foreign and local tourists. This study aims to determine the extent of tourism receipts & foreign tourists on economic growth in Indonesia. The method used in this study is a quantitative method, using secondary data from 1990-2020 in Indonesia. The analysis used is multiple regression analysis. The results of this study indicate that tourism receipts and foreign tourist arrivals have a positive and significant effect on GDP. The factors that have the most dominant influence on economic growth in Indonesia are the two independent factors, namely tourism receipts and foreign tourist arrivals.Keywords: Tourism Receipts, Foreign Tourist Arrivals, GDP, Economic Growth, Tourism